THE DEVELOPMENT OF STUDENT WORKSHEET BASED ON CORE (CONNECTING, ORGANIZING, REFLECTING AND EXTENDING) - Ririn Eva Hidayati (Universitas Negeri Surabaya, 2017)
The purpose of this research to determine the feasibility of student worksheet base on CORE(connecting, organizing, reflecting and extending) based on the validation data with the data sourcechemistry teacher and student responses to the data source. The design used was a model Researchand Development (R & D), where there is a stage and potential problems, data collection, design,study, revision, validation, and test student worksheet base on CORE. The results of the study designwas tested in the validation and limited so that it will produce a student worksheet base on CORE inaccordance with the standards of eligibility based on the feasibility of the content or materials,presentation and language. Student worksheet base on CORE that was developed has been validatedby two chemistry lectures and three teachers of chemistry and tested on 34 MAN 1 Kota Malangstudents. Achievement of the feasibility of the student worksheet base on CORE is the percentage ofthe overall aspects of the chemistry teacher assessment to validate that is equal to 98.15%, while thepercentage of student responses obtained at 98.52%.